CAFF Map No.56 - Distribution and observed trends of wild Rangifer populations throughout the circumpolar Arctic - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF International Secretariat, 2010)
CAFF Map No.56 - Distribution and observed trends of wild Rangifer populations throughout the circumpolar Arctic, 2010